Endometriosis and cancer: a systematic review and meta-analysis - Kvaskoff, M; Mahamat-Saleh, Y; Farland, LV; Shigesi, N; Terry, KL; Harris, HR; Roman, H; Becker, CM; As-Sanie, S; Zondervan, KT; Horne, AW; Missmer, SA (Oxford University Press, 2020)
BACKGROUND Endometriosis is an often chronic, inflammatory gynaecologic condition affecting 190 million women worldwide. Studies have reported an elevated cancer risk among patients with endometriosis. However, prior research has included methodologic issues that impede valid and robust interpretation.